Peptide-templated biomineralization of titanium dioxide toward improved light absorption and photodegradation activity. Issue 12 (7th November 2022) - Tsuchiya, Ryosuke; Murai, Kazuki
Abstract : TiO2 mineralization has been investigated by controlling morphology and crystal phase using organic templates, but the relationship between the molecular structure of the template and the functionality of the mineralized TiO2 has not been reported. Abstract : The mineralization of TiO2 has been previously investigated by controlling the morphology and crystal phase of TiO2 using several organic templates, but the relationship between the molecular structure of the template and the functionality of the mineralized TiO2 has not been reported. In this study, we investigated the influence and photodegradation activity of the TiO2 mineralized by different functional groups on the peptide template surface ( i.e., Ac-(Val-Lys-Val-Lys-Val-Glu)3 -CONH2 : KE, Ac-(Val-Lys-Val-Lys-Val-Ser)3 -CONH2 : KS, and Ac-(Val-Lys-Val-Lys-Val-Tyr)3 -CONH2 : KY). The KE–TiO2 and KS–TiO2 hybrids exhibited absorption only in the UV region (<380 nm), whereas the KY–TiO2 hybrid absorbed in a wider wavelength region that stretched into the visible spectrum (<500 nm). In addition, the KS–TiO2 hybrid showed a higher self-photosensitized degradation activity than the other systems owing to an efficient separation between electrons and holes, whereas the KY–TiO2 hybrid showed not only a reduction in self-photosensitized degradation activity due to the recombination between the methylene blue + ˙ radical cation (MB + ˙) and the injected electron, but also an increase in photocatalytic activity under UV or visible light irradiation. Our findings show that biomineralizing TiO2 presents an excellent and highly attractive approach to further functionalizing and optimizing TiO2 via an inexpensive and facile process, which will find use in all research fields that utilize TiO2 for such purposes.